(untitled) (Studia theodisca, 2025)
The aim of this essay is to explain the motto «Wir sind nichts; was wir suchen, ist alles» (We are nothing; what we search for is everything). This sentence can be shown to be essentially neoplatonic and central to Hölderlin’s thought in the areas of ontology, theology, politics and poetics. Thus, Hölderlin joins his neoplatonic contemporaries Hamann, Lessing, Herder, Goethe, Novalis, and Schleiermacher.